PEMODELAN PERTAMBAHAN TINGGI BADAN BALITA STUNTING DI KABUPATEN SOLOK DENGAN METODE REGRESI TOBIT KUANTIL BAYESIAN - Arfarani Rosalindari; Ferra Yanuar; Dodi Devianto (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study analyzes the model of stunting toddler height gain and its influencing factors with Bayesian Tobit Quantile Regression (BTQR). The data used in this study are secondary data in the form of height data for stunting toddlers in Solok Regency, West Sumatra in calculations conducted in August 2021 and February 2022 obtained from the Solok Regency Health Office, West Sumatra. After analyzing the height gain data with the BTQR method, it was found that the model at quantile 0.50 was the best model because it produced smaller MAE and RMSE values than other quantiles in estimating parameters with the BTQR method and it was found that the exclusive breastfeeding variable  and the Immunization variable  had a significant effect on the height gain of stunting toddlers